Lower limb biomechanical differences between jumps with different number of rotations in youth figure skaters - Koga, Ami; Bai, Xiaotian; Jia, Yuanyuan; Liu, Jingmin (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThe purpose of this study was to examine the differences in the lower-limb muscle activities and kinematics between figure skating Axel type jumps with different number of rotations in youth figure skaters. We hypothesized that skaters would exhibit increased lower limb flexion during jump propulsion phase, lower limb extension at take-off and greater muscle activation levels as jump rotation increases.MethodsEleven youth figure skaters (age: 12 ± 4.29 years; height: 146.82 ± 17.71 cm; body mass: 37.02 ± 14.47 kg) performed Waltz Jump (0.5 rotations), Single Axel Jump (1.5 rotations), and three of them additionally performed Double Axel Jump (2.5 rotations). Lower-limb kinematics were recorded using two high-speed cameras. Muscle activities of Rectus Femoris, Long Head of Biceps Femoris, Tibialis Anterior, Lateral Gastrocnemius, and Medial Gastrocnemius of both legs were measured. The differences between the jumps were compared using paired samples t-test. Comparison of EMG data between different muscles parts was performed by One-way ANOVA. Due to limited data, Double Axel jump was compared with descriptive analysis.ResultsMore difficult Axel type jump had higher jump height, shorter jump distance, faster jump take-off vertical velocity, and greater hip flexion during propulsion phase. The RMS and iEMG values of the left medial and lateral gastrocnemius and right tibialis anterior increased as the jump difficulty increased. Moreover, there were significant differences between different muscle parts RMS values and iEMG values in both Waltz jump and Single Axel jump (p < 0.01). Biceps femoris and rectus femoris indicated to have the highest RMS values and iEMG values in Waltz jump and Single Axel jump.ConclusionMore difficult Axel type jumps require greater hip flexion during propulsion phase and greater activities in hamstrings, quadriceps and tibialis anterior before jump take-off. Youth figure skaters can improve jump height, take-off vertical velocity and overall qualities of jumps by enhancing multi-joint movement, muscle coordination and take-off leg strength. These findings provide insights into the lower-limb biomechanical characteristics of figure skating jumps, and potentially leading to refinement of training programs for the youth figure skaters to optimize jump performances and to reduce potential lower extremity injuries.